SALIVARY BIOMARKERS FOR EARLY DIAGNOSIS OF PERIODONTAL DISEASE - Feruza Maxkamova (Modern American Journals, 2026)
Early identification of periodontal disease is essential to prevent progressive destruction of periodontal tissues and subsequent tooth loss. This study evaluates the diagnostic relevance of selected salivary inflammatory biomarkers for the early detection of periodontal pathology. A comparative clinical study was conducted involving periodontally healthy individuals and patients with early-stage periodontal disease. Unstimulated saliva samples were collected under standardized conditions, and the concentrations of interleukin-1β, tumor necrosis factor-α, C-reactive protein, and matrix metalloproteinase-8 were quantified using immunoassay-based techniques. Statistical analysis was performed to assess intergroup differences and diagnostic accuracy. The findings revealed significantly higher salivary levels of interleukin-1β, tumor necrosis factor-α, and matrix metalloproteinase-8 in the periodontal disease group compared to healthy controls (p < 0.05), while C-reactive protein showed a moderate increase. Receiver operating characteristic analysis demonstrated high sensitivity and specificity for interleukin-1β and matrix metalloproteinase-8. These results indicate that salivary inflammatory biomarkers offer a reliable, non-invasive approach for early periodontal disease diagnosis and may support improved screening and preventive strategies.
Keywords: Saliva; Periodontal disease; Salivary biomarkers; Early diagnosis; Inflammation